Peran Hukum Administrasi dalam Mewujudkan Kemandirian Desa Berdasarkan Kearifan Lokal - Arifin, Firdaus (Fakultas Hukum, Universitas Muslim Indonesia, 2024)
This study aims to analyze the role of State Administrative Law in realizing village autonomy based on local wisdom. The method used in this research was a qualitative approach with interviews, observations, and analysis of documents in some of the villages that were the subject of the study. These results show that State Administrative Law is vital in providing a foundation for villages to manage resources and development based on local potential and needs. Local wisdom is crucial for decision-making and resource management within villages, contributing to environmental sustainability and cultural preservation. The synergy between State Administrative Law and local wisdom creates effective policies that empower communities. Challenges in implementation, such as regulatory mismatches with local values, low legal literacy, and conflicts of interest, need to be addressed through legal socialization, capacity building, and collaboration. Therefore, it is recommended that the Government formulate inclusive and adaptive regulations to local wisdom and enhance human resource capacity in villages. Academics should conduct further research and provide policy recommendations. The private sector should play an active role in village economic empowerment, and village communities should actively participate in development and preserve local wisdom.